Pengaruh Likuiditas Dan Solvabilitas Terhadap Profitabilitas Pada PT KMI (Kabel Metal Indonesia) Wire and Cable Tbk Periode 2015-2024 - Ananda, Kiki; Janudin (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2025)
The purpose of this study is to determine the effect of Current Ratio and Debt to Equity Ratio on Net Profit Margin at PT KMI Wire and Cable, Tbk both partially and simultaneously. The method used is the Quantitative method. The sample used is the Financial Report of PT KMI Wire and Cable, Tbk for 10 years, namely 2015-2024. Data analysis uses classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing using SPSS 26 (Statictical Product and Service Solution 26). The results of this study are that the Current Ratio does not have a significant effect on the Net Profit Margin Determination Value or contribution of 5,3%. And the hypothesis test obtained a calculated t value <t table or (0,667 <2,364). This is strengthened by a significance value of 0,0523> 0,05. Debt to Equity Ratio has no effect The determination value or contribution of influence is 20,5% and the hypothesis test obtained the calculated t value > t table or (1,438 < 2,364). With a significance value of 0,188 > 0,05. Current Ratio and Debt to Equity Ratio have no significant effect on Net Profit Margin with a determination coefficient value of 23,6% while the remaining 76,4% is influenced by other factors. The hypothesis test calculated F value > F table or (1,078 < 4,74). This is also strengthened by a significance value of 0,391> 0,05.